Membangun Kemampuan Sosial Emosional Anak Usia Dini Melalui Media Video Sains - Rulismi, Dwi; Sari, Rika Partika; Nurwita, Syisva; Imran, Ranny Fitria; Aprianti, Monika; Paramita, Iluh Frensia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Building Early Childhood Social Emotional Skills Through Science Video Media discusses the importance of social emotional development in early childhood, which includes the ability to recognize, understand and manage emotions, and build positive relationships with others. These abilities are the foundation for children's success in learning and life, yet many young children still face limitations in this aspect. Science video media offers an innovative solution with engaging visual content and evocative narration, which not only builds curiosity towards science but also teaches social-emotional values through real-life situations. Despite its great potential, the implementation of this media faces challenges, such as the lack of understanding of educators and parents, limited technological infrastructure, and the risk of children's dependence on digital media. Through this community service program, educators and parents are educated on the use of science video media to create relevant, engaging, and holistic learning, which is expected to improve children's social-emotional abilities while strengthening the quality of education in the digital era.